2012
DOI: 10.3368/aoj.62.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Assessment of Children with Special Needs

Abstract: VA testing is of benefit in children with special needs to both their parents and ophthalmologists, providing quantitative information about visual impairment and reducing stress experienced by parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
(10 reference statements)
0
11
0
1
Order By: Relevance
“…Parents like to know how much their child can see, and use this to guide them in selection of suitable toys or stimulation equipment. It has been reported that the use of functional description to enhance the visual function assessment and provide child-specific information to the parents/carers is crucial in ensuring that the child achieves its potential 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Parents like to know how much their child can see, and use this to guide them in selection of suitable toys or stimulation equipment. It has been reported that the use of functional description to enhance the visual function assessment and provide child-specific information to the parents/carers is crucial in ensuring that the child achieves its potential 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Unrecognised visual needs can impact negatively on a child's development, cognitive and motor functions as well as physical well‐being, social interaction and academic attainment (Dudovitz et al, ; Morale et al, ; Roe, ; Salt & Sargent, ). It is, of course, important to meet visual needs for all children but it can be particularly difficult to achieve for children who have additional identified special educational needs.…”
Section: Discussionmentioning
confidence: 99%
“…Children without developmental disabilities have a much lower risk of visual impairment (0.16% compared to 10.5%) as well as other vision disorders (Salt & Sargent, ); children in special schools have reported prevalence of visual impairment between 12% and 16% (Little & Saunders, ). It is estimated that up to two‐thirds of children with visual impairments have other identified special educational needs, co‐occurring most frequently with neurological or developmental conditions such as autism, attention deficit/hyperactivity disorder or epilepsy (Morale et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmologists report the results to be useful in diagnosis and clinical management, while visual acuity testing was also associated with a reduction in parental stress. 52 TAC have therefore been demonstrated to provide useful data not only to orthoptists and ophthalmologists, but also to multi-disciplinary professionals involved in the care of special needs children.…”
Section: Altering the Investigative Proceduresmentioning
confidence: 99%